Developing a Hope Model Based on Cognitive Emotion Regulation Mediated by Spiritual Well-being in Patients with Heart Failure in Kermanshah and Its Effectiveness on Pain Tolerance - Safari, Shahin; Parandin, Shima; Akbari, Maryam (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to develop and validate a hope model based on cognitive emotion regulation with the mediating role of spiritual well-being in patients with heart failure, and to examine its effectiveness on increasing pain tolerance. Methods and Materials: This research was conducted in two phases. The first phase utilized a descriptive-correlational design to assess the relationships between cognitive emotion regulation, spiritual well-being, and hope among 270 heart failure patients in Kermanshah, Iran, selected via Cochran’s formula. In the second phase, a quasi-experimental design with pre-test–post-test and control group was employed. Thirty participants with low hope and spiritual well-being and high pain levels were selected and randomly assigned to an experimental group (receiving a structured hope-based educational program) or a control group. Data were collected using standardized questionnaires: Snyder’s Hope Scale, the Cognitive Emotion Regulation Questionnaire (CERQ), the Spiritual Well-Being Scale, and the McGill Pain Questionnaire. Data analysis was conducted using structural equation modeling (SEM) and ANCOVA through AMOS and SPSS version 23. Findings: The results revealed significant positive correlations among all key variables. Structural equation modeling confirmed the proposed model: cognitive emotion regulation significantly predicted hope both directly and indirectly through the mediating role of spiritual well-being. Model fit indices (e.g., χ²/df = 2.42, RMSEA = 0.068, CFI = 0.943) indicated good model fit. The ANCOVA results showed a significant group effect (F = 286.49, p < .001) of the hope-based intervention on increasing pain tolerance. Paired t-tests revealed a significant reduction in post-test pain scores in the experimental group compared to the control group. Conclusion: The study supports the effectiveness of a hope-based educational intervention grounded in cognitive and spiritual frameworks for enhancing psychological resilience and pain tolerance in patients with heart failure. The validated model offers a useful framework for designing future therapeutic interventions.